Good Governance of Thai Local Educational Management - Booranakit, Nipa (Animo Repository, 2018)
The purpose of this two-phase study is to develop guidelines for the leadership of educational administration of the Ministry of Interior Thailand Local Administration Organization(TLAO), and to identify the confirmatory factors for a good governance education management of Ministry of Interior TLAO. In order to identify the guideline of good governance, the methodology consisted of two phases: 1. Document analysis, and 2. Interview data analysis and confirmatory factor analysis. The interview data were synthesized into four categories of good governance: general criteria qualification, specific criteria qualification, systematic administration, and outstanding performance; and these underpinned the development of the 128-item survey questionnaire. Confirmatory Factor Analysis and correlation of causal model variables were carried out using multi-stage sampling. The confirmatory factor analysis indicated four confirmatory factors: the environment, input, process, and productivity, each weighing at 0.05 significance level. This result was confirmed by c2 = 162.61, c2/df = 0.99, df = 164, p value = 0.52, GFI = .96, AGFI = .94 and RMSEA = 0.000.